Online Signature Gathering for California Initiatives - Baer, Walter S.; Ulrich, Roy (Law, State and Telecommunications Review, 2012)
This paper discusses online signature gathering, beginning with the current process for qualifying California initiatives. It then describes how online signing of initiative petitions would work, how security and other objections could be addressed, and the pros and cons of adding this method of signature gathering to the initiative process.